2002
DOI: 10.1074/jbc.m200935200
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-restricted and Interferon γ-inducible Expression of the Allograft Inflammatory Factor-1 Gene Requires Pu.1

Abstract: Expression of allograft inflammatory factor-1 (Aif-1), a 17-kDa protein bearing an EF-hand Ca 2؉ binding motif, increases markedly in monocytes and macrophages participating in allo-and autoimmune reactions, including the perivascular inflammation in transplanted hearts, microglial infiltrates in experimental autoimmune neuritis, and the inflamed pancreas of prediabetic BB rats. To investigate the mechanism of this regulation, we isolated the mouse aif-1 gene and determined its genomic organization. The gene h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…As has become clear (Imai and Kohsaka 2002;Deininger et al 2002;Sibinga et al 2002), the Iba1 gene and protein, first mentioned in 1996 (Imai et al 1996), were originally discovered by several groups and independently named Iba1, microglial response factor-1 (MRF-1; Tanaka et al 1998), daintain (Chen et al 1997), and allograft inflammatory factor-1 (AIF-1; Utans et al 1995). Whereas studies of Iba1 and MRF-1 focused on their role in the brain and spinal cord, AIF-1 was first identified as a protein upregulated in cardiac allografts undergoing rejection (Utans et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…As has become clear (Imai and Kohsaka 2002;Deininger et al 2002;Sibinga et al 2002), the Iba1 gene and protein, first mentioned in 1996 (Imai et al 1996), were originally discovered by several groups and independently named Iba1, microglial response factor-1 (MRF-1; Tanaka et al 1998), daintain (Chen et al 1997), and allograft inflammatory factor-1 (AIF-1; Utans et al 1995). Whereas studies of Iba1 and MRF-1 focused on their role in the brain and spinal cord, AIF-1 was first identified as a protein upregulated in cardiac allografts undergoing rejection (Utans et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Also, some previous studies have demonstrated that AIF-1 plays a role in the inflammatory pathway of macrophages and lymphocytes [18][19][20][21]. In human coronary artery disease, AIF-1 is expressed in CD3-positive lymphocytes, and overexpression of AIF-1 enhances activation of lymphocytes, which suggests that AIF-1 plays a role in T-lymphocyte activation [21].…”
Section: Discussionmentioning
confidence: 96%
“…In vitro experiments showed that interferon gamma could up-regulate the expression of AIF-1 in macrophages. 15 Moreover, it was shown that macrophage cell line expressed a certain level of endogenous AIF-1 which could be enhanced by pro-inflammatory cytokines IL-1b or tumor necrosis factor-alpha. Macrophages stimulated with AIF-1 produced significantly increased amounts of IL-6, IL-10 and IL-12.…”
Section: Discussionmentioning
confidence: 99%